The distinctions and the value of physician-scientists: a call for sustained support and nourishment - Bruno Bezerril Andrade (Journal of Evidence-Based Healthcare)
CONTEXT: Physician-scientists occupy a unique and critical position at the intersection of clinical practice and scientific research, yet they are becoming increasingly rare due to systemic challenges, including time constraints, financial disincentives, and insufficient institutional support. This article explores the conceptual and historical differences between physicians, researchers, scientists, and physician-scientists, highlighting their distinct contributions to global health, policy-making, and medical innovation. Historical examples, such as Robert Koch and Virchow Rudolf, exemplify the transformative impact of physician-scientists in advancing medicine. The rise of artificial intelligence (AI) presents new opportunities and challenges for these professionals, as AI can enhance their dual roles in research and patient care. CONCEPTUALIZATION: However, to sustain and grow the physician-scientist workforce, significant changes are needed, including better financial incentives, protected research time, and stronger mentorship programs. Without such support, the future of medical innovation and global health may be jeopardized. This article advocates for a renewed focus on cultivating physician-scientists, emphasizing their indispensable role in bridging the gap between bench and bedside, and ensuring that scientific discoveries translate into tangible improvements in human health and well-being.